Glycosmis cymosa VAR. Simplicifolia (Kurz) Narayan -An Addition to the Flora of Garo Hills, Meghalaya - Bhuyan, T. C.; Biswas, S.A.S. (Indian Forester, 1991)
Glycosmis cymosa (Kurz) Naryanswamy, collected from Simsangiri Range of East Garo Hills is described in detail as an addition to the flora of Garo Hills.